Retórica intercultural y discurso académico - Heredero Zorzo, David (Vestnik za tuje jezike, 2017)
This paper presents the results of a study that, following the precepts of intercultural rhetoric, analyses research articles written in Spanish by Slovenian specialists. The study, framed within a larger research, focuses specifically on the rhetorical movements of the introductions following the CARS model (Swales, 1990, 2004). The results are analysed both quantitatively and qualitatively, contrasting them with those extracted from comparable research articles published by native researchers in Spanish and Slovene. The aim of the research is to establish criteria regarding the differences and similarities of the academic discourse of the Slovene researchers in relation to the native speakers of Spanish, pointing out where didactic applications to solve the existing disparities are needed, in order that their productions will be in line with the expectations of the audience to which they are directed.
Keywords: scientific texts; znanstvena besedila; raziskovanje; research; methodology; metodologija; Spanish; Spanish language; španščina; Slovene; Slovenian language; slovenščina; znanstveni jezik; academic discourse; academic writing; medkulturna retorika; intercultural rhetoric; korpusi (jezikoslovje); corpora (linguistics)